Implementasi Pembelajaran Berbasis Game untuk Meningkatkan Motivasi Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam di MA Yapina - Nurfalah, Samsu; Siti Nurhalimah; Rifa Salsabila; Siti Nursilah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Game-based learning has emerged as a relevant instructional strategy to address the challenges of 21st-century education, including in Islamic Religious Education (PAI), which is often perceived as monotonous and less engaging for students. This study aims to describe the implementation of game-based learning in enhancing students’ learning motivation in the PAI subject at MA Yapina. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that the use of educational games—both digital and non-digital—creates a more interactive and enjoyable learning atmosphere while encouraging active student participation. Students demonstrated increased motivation, self-confidence, and interest in understanding religious concepts more deeply. In addition to boosting motivation, game-based activities contributed to better conceptual understanding through collaborative tasks and contextual simulations of Islamic values. However, several challenges were identified, including limited teacher competence in using game-based media and unequal availability of technological facilities. These findings suggest that game-based learning holds significant potential for PAI instruction but requires adequate teacher support and sufficient infrastructure to optimize its implementation. This study is expected to serve as a reference for developing innovative and creative learning strategies in Islamic Religious Education that align with the characteristics of digital-native learners.